2020
DOI: 10.1038/s41598-020-63353-5
|View full text |Cite
|
Sign up to set email alerts
|

RAC1-Dependent ORAI1 Translocation to the Leading Edge Supports Lamellipodia Formation and Directional Persistence

Abstract: Tumor invasion requires efficient cell migration, which is achieved by the generation of persistent and polarized lamellipodia. The generation of lamellipodia is supported by actin dynamics at the leading edge where a complex of proteins known as the WAVE regulatory complex (WRC) promotes the required assembly of actin filaments to push the front of the cell ahead. By using an U2OS osteosarcoma cell line with high metastatic potential, proven by a xenotransplant in zebrafish larvae, we have studied the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 65 publications
2
10
0
Order By: Relevance
“…Similarly, a study reported that activation of transient receptor potential melastatin 2 (TRPM2) Ca 2+ channel by H 2 O 2 in Hela and prostate cancer (PC)-3 cells resulted in filopodia formation, loss of stress fibers, and disassembly of focal adhesion that eventually caused an increase in cell migration [ 66 ]. Another study on highly metastatic osteosarcoma cell line U2OS reported that Ca 2+ channel ORAI1 translocation to the leading edge was essential for formation of lamellipodia and cell directionality [ 67 ]. Our data are in good agreement with these findings and points to the importance of PMCA4b in mediating actin cytoskeleton rearrangement and cell motility through controlling cytosolic Ca 2+ levels.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study reported that activation of transient receptor potential melastatin 2 (TRPM2) Ca 2+ channel by H 2 O 2 in Hela and prostate cancer (PC)-3 cells resulted in filopodia formation, loss of stress fibers, and disassembly of focal adhesion that eventually caused an increase in cell migration [ 66 ]. Another study on highly metastatic osteosarcoma cell line U2OS reported that Ca 2+ channel ORAI1 translocation to the leading edge was essential for formation of lamellipodia and cell directionality [ 67 ]. Our data are in good agreement with these findings and points to the importance of PMCA4b in mediating actin cytoskeleton rearrangement and cell motility through controlling cytosolic Ca 2+ levels.…”
Section: Discussionmentioning
confidence: 99%
“…Actin polymerization regulated by Rac1 and Cdc42 can promote cell movement, leading to migration and invasion (19). The migration of cancer cells is closely related to the decrease of cell adhesion, rearrangement of cytoskeleton, degradation of the extracellular matrix and the formation of cell surface protrusions, which are the key factor affecting the migration of cancer cells (20). Extension of cytoplasm in the movement direction is the first step of cell movement.…”
Section: Rac1 Regulates Cell Adhesion Morphology and Movementmentioning
confidence: 99%
“…MERTK can activate phospholipase C γ2 which can lead to DAG and IP3 production, thus triggering Ca 2+ release and PKC mediated Rac1 cytoskeletal rearrangement ( Todt et al, 2004 ). Additionally, a recent study demonstrated Rac1 potentiated ORAI1 translocation to the leading edge of migrating cells ( Lopez-Guerrero et al, 2020 ). The localized Ca 2+ dynamics observed in our study are likely due to cytoskeletal remodeling during astrocyte phagocytosis.…”
Section: Discussionmentioning
confidence: 99%